The Burden of Progressive Fibrosing Interstitial Lung Disease: A DELPHI Approach - Wuyts, Wim A. (Adv Ther, 2020)
INTRODUCTION: The term progressive fibrosing interstitial lung disease (ILD) describes patients with fibrotic ILDs who, irrespective of the aetiology of the disease, show a progressive course of their disease despite current available (and non-licensed) treatment. Besides in idiopathic pulmonary fibrosis, little is known about management and the burden of patients with fibrotic ILD, particularly those with a progressive behaviour. METHODS: Using the Delphi method, 40 European experts in ILD management delivered information on management of (progressive) fibrosing ILD and on the impact of the disease on patients’ quality of life (QoL) and healthcare resource utilisation (HCRU). Annual costs were calculated for progressive and non-/slow-progressive fibrosing ILD for diagnosis, follow-up management, exacerbation management, and end-of-life care based on the survey data. RESULTS: Physicians reported that progression in fibrosing ILD worsens QoL in both patients and their caregivers. Progression of fibrosing ILD was associated with a greater use of HCRU for follow-up visits and maintenance treatment compared with the non-/slow progression. The number of patients who suffered at least one acute exacerbation was reported to be more than three times higher in progressive fibrosing ILD patients than in patients with non-/slow-progressive fibrosing ILD. On average, annual estimated costs of progressive fibrosing ILD per patient were 1.8 times higher than those of the non-/slow-progressive form of the disease. CONCLUSIONS: Progression in fibrosing ILD causes a significant impact on QoL and HCRU and costs. These survey data underline the need for safe and effective therapies to slow the disease progression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12325-020-01384-0) contains supplementary material, which is available to authorized users.